2016
DOI: 10.1111/cei.12888
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of new single polymorphisms in the T helper type 17 pathway for psoriasis in the Korean population

Abstract: Psoriasis is a polygenic and multi-factorial disease showing ethnic differences in terms of its severity and frequency. Therapies targeting interleukin (IL)-17A, IL-17 receptor (IL-17R) and Janus kinases (JAKs) are in clinical development for the treatment of psoriasis, and their success suggests the essential role of these molecules in psoriasis. To investigate the genetic susceptibility in T helper type 17 (Th17) cell signal transduction pathways for promoting psoriasis, we performed candidate gene and linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 36 publications
1
25
3
Order By: Relevance
“…They demonstrated that the IL-17F polymorphism rs763780 T/C is strongly associated with psoriasis (1). The study found no association between the five evaluated polymorphism of IL-17RA or with the other evaluated polymorphisms and psoriasis (1).…”
Section: Polymorphisms Of Il-17contrasting
confidence: 55%
See 3 more Smart Citations
“…They demonstrated that the IL-17F polymorphism rs763780 T/C is strongly associated with psoriasis (1). The study found no association between the five evaluated polymorphism of IL-17RA or with the other evaluated polymorphisms and psoriasis (1).…”
Section: Polymorphisms Of Il-17contrasting
confidence: 55%
“…IL-17F polymorphism rs763780 is strongly associated with psoriasis in Korean population (1), with a good response to treatment with infliximab and with no response to treatment with adalimumab or ustekinumab in Caucasian population (32). On the other hand, no association between this polymorphism and the disease was found in Japanese and Spanish population (4,16).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Majority of the detected somatic mutations, including our patient, involved the 683rd amino acid residue, which is an important amino acid for the JH2 domain-mediated negative autoregulation of JAK2 activity (32). The second somatic mutation associated with the JAK pathway regulation was a variant of interleukin-17 receptor (IL17RC) gene (33). Nucleoporin 214 (NUP214) is required for cell cycle and nucleocytoplasmic transport.…”
Section: Discussion Of the Underlying Pathophysiology And Significancmentioning
confidence: 88%